PEMBERDAYAAN MASYARAKAT ISLAM MELALUI BIMBINGAN KEAGAMAAN DI KAMPUNG PUEH, SEMATAN, MALAYSIA - Safitri , Ayu; Nunung, Nunung; Sofia, Sofia; Muhammad , Rifqi; Manja, Manja (Borneo : Journal of Islamic Studies, 2023)
The aim of this study is to describe community empowerment through religious guidance in Kampung Pueh, Sematan, Sarawak, Malaysia, in 2023. The research method uses a qualitative-descriptive approach. Data collection was done using interview guidelines aimed at informants, namely Iran as the Pueh Village Leader, Muhammad Asnizan Mahadi as the Manager of Baitul Quddus Shrine, and Nurhayati binti Jali as an empowerment participant. The results of the research in this study are that empowerment activities through religious guidance were carried out in Pueh Village, namely 1) The place of implementation of empowerment at Surau Baitul Quddus; 2) the target of empowerment is converts (new brothers); 3) form of activity through Yasin reading Yasin Friday night, Knowledge Assembly, Learning to read the Koran and Iqra; The obstacle is that not everyone can attend each activity because they are busy. Lack of syiar in learning programs to read the Koran and Iqra; Lack of counseling for learning the Koran and Iqra, including counseling about why you should learn, the benefits of learning, and the disadvantages of not learning; 5) Supporting this is a strong desire to learn religion. 5) Supporting it is a strong desire to learn religion.